Assessing the impact of including leaflets in the simulation of TAVI deployment into a patient-specific aortic root. Issue 7 (18th May 2016) - Bailey, Jonathon; Curzen, Nick; Bressloff, Neil W.
Abstract : Computational simulation of transcatheter aortic valve implantation (TAVI) device deployment presents a significant challenge over and above similar simulations for percutaneous coronary intervention due to the presence of prosthetic leaflets. In light of the complexity of these leaflets, simulations have been performed to assess the effect of including the leaflets in a complete model of a balloon-expandable TAVI device when deployed in a patient-specific aortic root. Using an average model discrepancy metric, the average frame positions (with and without the leaflets) are shown to vary by 0.236% of the expanded frame diameter (26 mm). This relatively small discrepancy leads to the conclusion that for a broad range of replacement valve studies, including new frame configurations and designs, patient-specific assessment of apposition, paravalvular leakage and tissue stress, modelling of the prosthetic leaflets is likely to have a marginal effect on the results